The RANCANG BANGUN APLIKASI SISTEM INFORMASI DAN PENDISTRIBUSIAN AYAM PEDAGING DI KABUPATEN KAMPAR BERBASIS WEB ( STUDI KASUS : PT. SEMESTA MITRA SEJAHTERA (SMS)) (PROGRAMMING) - Yanti, Refni Rizma; Munti , Novi Yona Sidratul; Adeswastoto, Hanantatur (Jurnal Inovasi Teknik Informatika, 2023)
ABSTRACT Provision of information about the availability of broiler PT. Semesta Mitra Sejahtera in Kampar Regency is still done manually by calling all distributors who have subscribed. In storing order data it is also still manual by recording on paper and typing it back into Microsoft Excel, this is of course very difficult for the admin because there is a lot of data that must be entered. So a support system was created in providing information and storing chicken order data to make it more time and cost efficient.Making this system uses data collection methods by taking data at PT. Prosperous Partner Universe.The support system is made web-based using the PHP programming language development tools, Laravel framework, MySQL, Visual Studio Code, and HTML. Keywords: Information system, PT. Semesta Mitra Sejahtera, broiler, web